Theories and Models of Urbanization. Geography, Economics and Computing Sciences. - (:unkn) unknown (Springer, 2020)
This book provides a thorough discussion about fundamental questions regarding urban theories and modeling. It is a curated collection of contributions to a workshop held in Paris on October 12th and 13th 2017 at the Institute of Complex Systems by the team of ERC GeoDiverCity. There are several chapters conveying the answers given by single authors to problems of conceptualization and modeling and others in which scholars reply to their conception and question them. Even, the chapters transcribing keynote presentations were rewritten according to contributions from the respective discussions. The result is a complete “state of the art” of what is our knowledge about urban processes and their possible formalization.
Keywords: Stadtentwicklungsforschung; Stadtsystem; Urbanisierung; Steuerung; Stadtgeografie; Stadttheorie; Stadtökologie; Stadtwachstum; Wohnungsbau; Bauboom; Systemanalyse; Schwellenland; Modellierung; Skalierung; Maßstabseffekt; International